Proposal of framework for the validation of industrial symbiosis indicators using agent-based modeling - Mantese, Gabriel Couto (2018)
Industrial symbiosis is crucial to the formation of the eco-industrial parks. Several performance indicators have been proposed for measuring and monitoring the industrial symbiosis. The current focus of researches is on the proposal of these indicators, while it is still necessary to validate them, so they can become more robust and reliable. However, there is no specific validation methodology for this type of indicator. The central objective of this research was to develop a methodology specific for the analysis of industrial symbiosis indicators. The work resulted in a framework for the validation of industrial symbiosis indicators with the differential of combining the conceptual validation, based on the technical and theoretical information on the indicator, and the empirical validation, based on the analysis of the indicated behavior. The framework is composed of a set of activities and artifacts that support all validation steps, which includes a set of specific validation criteria for industrial symbiosis indicators, and a simulation model developed through the agent-based modeling technique, which is able to simulate all the industrial symbiosis indicators available in the literature, allowing the comparison between them. The specific validation criteria were verified through the judgment of experts in the validation of an indicator, the Industrial Symbiosis Indicator; and the simulation model was proposed and used for the comparison between all the indicators, being possible to identify their characteristics in different scenarios. By combining the two strategies, a validation instrument with significant progress in relation to the state of the art is reached; it can support researches in the proposal of new indicators.